Clinical characteristics of familial dysalbuminemic hyperthyroxinemia in Chinese patients and comparison of free thyroxine in three immunoassay methods - Zhao, Linlin; Zhou, Yingying; Huang, Fengjiao; He, Xiaoyang; Mei, Guili; Wang, Shoujun; Zhao, Yanyan (Frontiers in Endocrinology, 2023)
Objective Familial dysalbuminemic hyperthyroxinemia (FDH) has not been thoroughly studied in the Chinese population to date. The clinical characteristics of FDH in Chinese patients were summarized and the susceptibility of common free thyroxine (FT4) immunoassay methods evaluated. Methods The study included 16 affected patients from eight families with FDH admitted to the First Affiliated Hospital of Zhengzhou University. The published FDH patients of Chinese ethnicity were summarized. Clinical characteristics, genetic information and thyroid function tests were analyzed. The ratio of FT4 to the ULN (FT4/ULN) in three test platforms were compared in patients with R218H ALB mutation from our center. Results The R218H ALB mutation was identified in seven families and the R218S in one family. The mean age of diagnosis was 38.4 ± 19.5 years. Half of the probands (4/8) were misdiagnosed as hyperthyroidism previously. The ratios of serum iodothyronine concentration to ULN in FDH patients with R218S were 8.05-9.74 for TT4, 0.68-1.28 for TT3 and 1.20-1.39 for rT3, respectively. The ratios in patients with R218H were 1.44 ± 0.15, 0.65 ± 0.14 and 0.77 ± 0.18, respectively. The FT4/ULN detected using the Abbott I4000 SR platform was significantly lower than Roche Cobas e801 and Beckman UniCel Dxl 800 Access platforms (P＜0.05) in patients with R218H. In addition, nine Chinese families with FDH were retrieved from the literature, of which eight carried the R218H ALB mutation and one the R218S. The TT4/ULN of approximately 90% of patients (19/21) with R218H was 1.53 ± 0.31; the TT3/ULN of 52.4% of patients (11/21) was 1.49±0.91. In the family with R218S, 45.5% of patients (5/11) underwent TT4 dilution test and the TT4/ULN was 11.70±1.33, and 90.9% (10/11) received TT3 testing and the TT3/ULN was 0.39±0.11. Conclusions Two ALB mutations, R218S and R218H were found in eight Chinese families with FDH in this study, and the latter may be a high-frequency mutation in this population. The serum iodothyronine concentration varies with different mutation forms. The rank order of deviation in measured versus reference FT4 values by different immunoassays (lowest to highest) was Abbott < Roche < Beckman in the FDH patients with R218H.